The effect of a health belief-based educational intervention on the COVID-19 preventive behaviors among young people - Reza Masoudi; Betul Gholamian Dehkordi; Narges Asgari; Zahra Fazel; Leili Rabiei (Payesh, 2023)
Objective (s): The Covid 19 pandemic is highly contagious and may increase the likelihood of transmitting the disease to others especially to young people. Therefore, raising the awareness of young people about the preventive behaviors of the Covid 19 is very important. The present study was conducted with the aim of assessment of the effectiveness of a program based on the Health Belief Model on the promotion of preventive behaviors of Covid 19 in young people. Methods: This was a quasi-experimental study that was conducted among a sample of young married people aged 25-35 years in Shahrekord, Iran by simple random sampling method.  For the intervention group, 6 virtual training sessions were held based on the structures of the health belief model during one month. Data collection tools included demographic information, a questionnaire based on health belief model constructs and a questionnaire of preventive behaviors. Data analysis was performed using SPSS software version 18. Results: In all we recruited 100 young people into the study (50 in intervention and 50 in control groups). The results showed that there was no significant difference between the dimensions of the health belief model in the two groups before the intervention (P <0.05). This difference was significant in the assessment one month after the intervention (P <0.05). Regarding the structure of perceived barriers, despite the decrease in the mean score, this difference was not significant (P = 0.07). Also, there was no significant difference in the mean scores of preventive behaviors between the two groups before the intervention (P <0.05), while this difference was significant in the 1-month measurement (P <0.05). Conclusion: The implementation of a program based on the Health Belief Model raises the level of awareness and, consequently, creates favorable attitudes towards performing Covid 19 preventive behaviors.